Assessment of first-year students’ metacognitive ability in Faculty of Medicine, Universiti Sultan Zainal Abidin (UniSZA): Toward curriculum development - Uday Younis, Hussein; Nor Iza, A.rahman; Nordin, Simbak; Shahid, Hassan; Tg. Fatimah Murniwati, Tg.Muda (2017)
Introduction: Metacognition is the awareness of knowledge how one learns in addition to what one learns and to understand how a task will be performed. Metacognitive skill as self-assessment is recognised as an important contributor to the development of critical capacity, reflective attitude and autonomous life-long learning. Accurate, self-assessment of knowledge and skills is essential for students to maintain and improve through self-directed learning. Objective: The objective of this study was to explore, how well students’ evaluate their own level of understanding for lectures to reflect their metacognitive skill that can be used in educational strategy to promote students’ personal and professional growth. Methods: To assess the metacognition of the students, a questionnaire based on three items was designed. All 60 (17 male and 43 female) preclinical, first-year medical students were included in this study. The metacognition as planning, monitoring and evaluating the lecture was judged through students’ response on 33 lectures in terms of understanding of knowledge, clearing of misconceptions and presenting of a well prepared material respectively in the field of haematology and parasitology. Metacognition as reflected in the lecture understanding level (LUL) score, lectures preparation level (LPL) score and students question level (SQL) score was estimated for its correlation with student’ achievement score in pre-clinical phase of MBBS program. Results: The data was analysed for correlation between metacognition and overall students’ achievement scores and a statistically significant correlation between LUL and multiple true false (MTF) of 268 (p = .039), LPL and MTF of .282 (p = .029) as well as between SQL and MTF of .360 (p = .005) was compared to poor correlation between LUL, LPL and SQL and the other three assessment tools (short essay questions [SEQ], problem-based questions [PBQ] and objectively structured practical examination [OSPE]) was found. Conclusion: The significant correlation of students’ metacognition and their achievement score in classroom setting with MTF and poor correlation with SEQ, PBQ and OSPE is attributed to multiple factors discussed in this study, imperative to students’ personal and professional growth.